Upright spins examined - Thibert, H. (The Professional Skater PS Magazine, 2009)
Biomechanical analysis of the spinning edge change and the body mechanics during the upright spin. Model of the spin rotation and graphical representation of the spin tracings with the applied edge and body forces are shown.